ToP-DNJ, a selective inhibitor of endoplasmic reticulum α-glucosidase II exhibiting anti-flaviviral activity - Kiappes, JL; Hill, ML; Alonzi, DS; Miller, JL; Iwaki, R; Sayce, AC; Caputo, AT; Kato, A; Zitzmann, N (American Chemical Society, 2017)
Iminosugars have therapeutic potential against a range of diseases, due to their efficacy as glycosidase inhibitors. A major challenge in the development of iminosugar drugs lies in making a compound that is selective for the glycosidase associated with a given disease. We report the synthesis of ToP-DNJ, an antiviral iminosugar-tocopherol conjugate. Tocopherol was incorporated into the design of the iminosugar in order to direct the drug to the liver and immune cells, specific tissues of interest for antiviral therapy. ToP-DNJ inhibits ER α-glucosidase II at low micromolar concentrations and selectively accumulated in the liver in vivo. In cellular assays, the drug showed efficacy exclusively in immune cells of the myeloid lineage. Taken together, these data demonstrate that inclusion of a native metabolite into an iminosugar provides selectivity with respect to target enzyme, target cell and target tissue.